Some solutions for enhancing the effectiveness of studies in field of social sciences in Vietnam - Tuan, Nguyen Quang (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT)
The effectiveness of studies in the field of social sciences is the obtained result of research activities in comparison to the initially set-up targets. This effectiveness is affected by numerous factors, internal and external research activities. This paper is focused on analysis of some solutions to enhance the effectiveness of studies in field of social sciences in Vietnam. Code: 12020701